Impact of the shift from face-to-face to virtuality in higher education (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The present work deals with the impact of the change from face-toface to virtuality in the face of the Covid-19 pandemic as a driver ofICTs in higher education, in which everything related to the use ofICTs will be shown and how currently they are being the protagonistsof the activities in higher education so that it can continue its coursein the midst of the pandemic, the measures taken to safeguard thesafety of the entire university community by its authorities will beshown, one of them is confinement or forty to prevent theircommunity from being exposed to Covid-19 contagion and so thatacademic activities can continue, it was decided to make use of ICTsin a very significant way since it is currently the most feasible way, wewill have concepts, data both of Covid-19, ICTs, Higher Education, aswell as the use of ICTs. In this work we can also find surveys carriedout on both students and teachers about ICTs in higher education inquarantine, we will indicate our appreciation of the academicprocesses and the benefits of the use of technologies.